Facebook to facilitate instructor roles in course-related online interaction: a pilot study - Al-Dheleai, Y. M. (Asian Research Publishing Network, 2016)
The popularity of Facebook as the most used platform among university youth made it an acceptable platform for professional purposes. The use of Facebook for educational purpose is becoming more accepted to facilitate and ease online interaction with the learning participants. The purpose of this study is to investigate students’ expectations towards the instructor role in learning interaction through Facebook and its correlation with students’ academic performance. Quantitative data was collected from the respondents through survey method of data collection. The findings of the study reveal that students have positive expectations of instructor role on Facebook interaction. Additionally, the findings reveal that there are a correlation between instructor role of facilitating discourse and direct instruction with students’ academic performance.